Hidden Nickel Deficiency? Nickel Fertilization via Soil Improves Nitrogen Metabolism and Grain Yield in Soybean Genotypes - Siqueira Freitas, Douglas; Wurr Rodak, Bruna; Rodrigues dos Reis, André; de Barros Reis, Fabio; Soares de Carvalho, Teotonio; Schulze, Joachim; Carbone Carneiro, Marco A.; Guimarães Guilherme, Luiz R. (Frontiers in Plant Science, 2018)
Nickel (Ni) - a component of urease and hydrogenase - was the latest nutrient to be included in the list of essential elements to plants. Although relevant studies have been performed concerning its essentiality, there are no records of Ni deficiency for annual species cultivated under field conditions. The reason might be the nonappearance of obvious symptoms, i.e., a hidden (or latent) deficiency. Soybean, a crop cultivated on soils poor in available Ni content, has a high dependence on biological nitrogen fixation, in which Ni plays a key role. Thus, we hypothesized that Ni fertilization in soybean genotypes results in a better physiological status and in higher grain production due to the hidden deficiency of this micronutrient. To verify this hypothesis, two simultaneous experiments were carried out, under greenhouse and field conditions, with fertilization of 0.0 or 0.5 mg of Ni kg-1 of soil. For this, we have used 15 soybean genotypes and two soybean isogenic lines (urease positive, Eu3; urease activity-null, eu3-a, formerly eu3-e1). Plants were evaluated for yield, Ni concentration, N concentration, photosynthesis, and N metabolism. Nickel fertilization resulted in greater grain yield in some genotypes, evidencing the hidden deficiency of Ni in both conditions, i.e., greenhouse and field. Increasing yields were associated with a high efficiency of N metabolism, namely, a higher leaf concentration of ureides and ammonia. Nitrogen compounds allowed also separation of the genotypes into different ‘responsiveness groups’ to Ni supply. Ni fertilization also promoted leaf N concentration and positively affected the photosynthesis in the genotypes, never causing detrimental effects, except for the eu3-a mutant. Due to the absence of ureolytic activity, eu3-a had a high leaf urea accumulation, coinciding with lower yield. In summary, the effect of Ni on the plants was positive and the extent of this effect was controlled by genotype-environment interaction. The application of 0.5 mg kg-1 of Ni resulted in safe levels of this element in grains for human health consumption. Including Ni applications in fertilization programs may provide significant yield benefits in soybean production. This might also be the case for other annual crops, especially legumes.